Effect and UtilIzation of Crude oil on Some of Fungi Isolated From Soil - Shafiq, Sh. A.; Mizil, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was conducted to reveal the effect of crude oil on some fungal species isolation from soil in order to evaluate the role of these fungi in environmental balance of soil . The results showed a variation in numbers and percentage of the fungal isolates Aspergillus fumigatus dominated over all isolates with a frequency of (32.47) . In respect of the effect of different concentrations of the crude oil, low concentrations (0.05, 0.1) % showed no effect on radial growth ( mean colony diameter) of the isolated fungi grown on solid media , whereas other concentrations (5.10)% showed gradual toxic effect on these fungi . The fungus Aspergillus fumigatus reveal higher sensitivity against all concentrations of the crude oil compared to others species , The results showed also variation of these fungi in utilization of the crude oil on solid mineral media used as a sole carbon and energy source with the different concentrations of the crude oil , exposing time and kind of species.